Renal function and plasma volume following utramarathon cycling - Neumayr, G.; Pfister, R.; Hörtnagl, H.; Mitterbauer, G.; Prokop, W.; Joannidis, M. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
extreme ultramarathon cycling is not available. It was the objective to evaluate the renal and haematological effects of ultraendurance cycling in the world's best ultramarathon cyclists. Methods Variables of renal function and of volume status, e.g. creatinine (CR), urea, haemoglobin (Hb), haematocrit (Hct), plasma volume (PV), were investigated in 16 male ultramarathon cyclists during the 1st Race Across the Alps in 2001 (distance: 525 km; cumulative altitude difference: 12,600 m). Results All renal functional parameters were normal pre-exercise. During the race serum CR, urea and uric acid rose significantly by 33, 97% and 18% (p<0.001 respectively) and nearly normalised again on the following day. The decline in calculated CR clearance was 25%. There was a negative correlation (r=.0.575, p=0.02) between the rises in serum CR and the athlete's training kilometers. The serum urea/CR ratio rose above 40 in 12 athletes (75%). Mean fractional sodium excretion and fractional uric acid excretion fell below 0.5% (p<0.001) and 7%, indicating reduced renal perfusion. The deflection of the renal functional parameters was temporary and nearly gone after 24 hours of recovery. Hct declined during the race from 0.44 to 0.42, and continued falling on the next day (0.42 to 0.40; p<0.001). The corresponding rises in calculated PV were +8% and +22%. Discussion/Conclusion The study affirms that in world class cyclists the enormous strains of ultramarathon cycling influence renal function only on a minimal scale. The impact on the PV, however, is pronounced leading to marked haemodilution post-exercise. This very temporary "impairment of renal function" seems to be the physiological response to ultramarathon cycling and may be attenuated to some extent by preceding high-volume training.